Need of National Computer Data Bank for the Indigenous Farm-Management-Information-Technology with a Slant to Information Technology in Agricultural Sciences - Bankapur, M. B. (Journal of Information and Knowledge, 1987)
There is a tremendous flow of "know-how" of the indigenous farm information technology which is not properly stream-lined and logically trimmed. This knowledge has not been best-served with the methodology of systems research; conception, construction, validation and exploitation of computer based simulation models in direct relevance to agricultural sciences. technology and management. The object of ARIC (- Agricultural Research Information Centre) of ICAR has not been fully exploited and needs review. This paper suggests for separate "National Computer Data Bank for the indigenous Farm-Management-Information-Technology" with a slant to "Information-Technology" in Agricultural Sciences". Emphasises the need to start exclusively "Indian Agricultural Abstracts" to keep alive and conventional methods of dissemination and utilization of information on the coverages of agricultural literature in "Indian Science Abstracts" is not upto the mark. It also stresses the unique feature of "Extension Information" and "Information Science" two-in-one for a broad based information data bases at the National level in ICAR, New Delhi.